Common Commercial Policy and Member States’ Playing Fields - Nagy, Csongor (The Policies of the European Union from a Central European Perspective, 2022)
This chapter analyzes the playing field afforded by the EU exclusive competence over commercial policy to the Member States to develop an independent policy in relations to extra-EU trade. First, the chapter presents the primary elements of the EU’s ‘constitutional authorization.’ particularly regarding investments, where the EU is less omnicompetent. Second, the nature of international economic relations is presented. This section shows that the focus of international commercial policy shifted from traditional restrictions of trade to regulatory trade barriers. Third, the elements of the EU’s commercial policy and the Member States residual powers are presented to elucidate how the Member States may engage in commercial policy notwithstanding the exclusive EU competence. This section shows that, on the one hand, the margins of commercial policy are somewhat unclear, and, on the other hand, there are regulatory questions that are legally not part of the common commercial policy but do have an impact with trade with non-EU countries and, hence, giving a chance to Member States to develop an independent national policy toward extra-EU trade. Keywords: common commercial policy, extra-EU trade, internal market, international trade, intra-EU trade, investment protection, WTO